Ethanol Extract of Marigold Flower (Tagetes Erecta L.) Decreases The Total Cholesterol, Low Density Lypoprotein (LDL), Malondialdehyde (MDA), and Apoliprotein B (APOB) on Hyperlipidemia Rat Models - Kresnapati, I Nyoman Bagus Aji; Khaerunnisa, Siti; Safitri, Indri (Folia Medica Indonesiana, 2021)
This study aimed to determine the effect of ethanol extract of gemitir flower (Tagetes erecta L.) on total cholesterol levels, Low-Density Lipoprotein C (LDL), Malondialdehyde (MDA), Apolipoprotein B (ApoB). Forty-eight Rattus norvegicus were randomly divided into 6 groups, groups were given standard feed (K-) and 5 groups of hyperlipidemia models (K +, P1, P2, P3, P4) were given High Fat Diet (HFD) for 35 days. On the 36th day, the total cholesterol levels were checked through the tail of Rattus norvegicus, and from day 37 to day 50 were given a normal diet (K-), HFD (K +), simvastatin 10 mg/kgBW (P1), ethanol extract of gemitir flowers (Tagetes erecta L.) 200 (P2), 400 BW (P3), and 800 mg/kgBW (P4). On day 51, the total cholesterol, LDL-C, MDA, and ApoB blood serum levels were checked. The results showed total cholesterol, Low-Density Lipoprotein (LDL), Malondialdehyde (MDA), and Apolipoprotein B (ApoB) given ethanol extract of gemitir flowers 200 and 400 mg/kgBW (P2) had a significant reduction (P < 0.05). Giving ethanol extract of gemitir flower (Tagetes erecta L.) could reduce levels of total cholesterol, LDL, MDA, and Apo B.